Bone-Targeted Nanoparticle Drug Delivery System: An Emerging Strategy for Bone-Related Disease - Chen, Yulin; Wu, Xianmin; Li, Jiadong; Jiang, Yingying; Xu, Ke; Su, Jiacan (Frontiers in Pharmacology, 2022)
Targeted delivery by either systemic or local targeting of therapeutics to the bone is an attractive treatment for various bone metabolism diseases such as osteoporosis, osteoarthritis, osteosarcoma, osteomyelitis, etc. To overcome the limitations of direct drug delivery, the combination of bone-targeted agents with nanotechnology has the opportunity to provide a more effective therapeutic approach, where engineered nanoparticles cause the drug to accumulate in the bone thereby improving efficacy and minimizing side effects. Here, we summarize current advances in systemic or local bone targeting approaches and nanosystem applications in bone diseases, which may provide new insights into nanocarrier-delivered drugs for the targeted treatment of bone diseases. We envision that novel drug delivery carriers developed based on nanotechnology will be a potential vehicle for the treatment of currently incurable bone diseases and are expected to be translated into clinical applications.